PEMBERIAN INSENTIF, PENDIDIKAN PELATIHAN DAN KINERJA - Ernawati, Ernawati; Sujianto, Sujianto; Heriyanto, Meyzi (Jurnal Ilmu Administrasi Negara, 2018)
Incentives, Training and Performance Education. The purpose of this study is to know how the influence of partial and simultaneous variables from the provision of incentives and training education on the performance of high school teachers in Kampar District Tambang District. This research uses quantitative descriptive method. The population of research is SMA / SMK Kecamatan Tambang as many as 140 people. Samples counted 63 people by using purposive sampling technique. Data collection techniques are questionnaires, interviews and observations. Data analysis techniques use multiple linear regression. The results showed that there was a significant influence between the incentives to teachers on the performance of high school teachers in Kampar District Mining Subdistrict and there was also a significant influence between the variables of training education on the performance of high school teachers in Kampar District Tambang District. Simultaneously incentives and training education have an effect on to the performance of high school teachers in Kecamatan Tambang Kabupaten Kampar with a very significant level of influence. Where from determination test of R2 known that incentive variable and training education have influence equal to 68,6% and rest of 31,4% influenced by variable not examined in this research.